Properties, Structures, and Physiological Roles of Three Types of Anion Channels Molecularly Identified in the 2010’s - Okada, Yasunobu; Sabirov, Ravshan Z.; Merzlyak, Petr G.; Numata, Tomohiro; Sato-Numata, Kaori (Frontiers in Physiology, 2021)
Molecular identification was, at last, successfully accomplished for three types of anion channels that are all implicated in cell volume regulation/dysregulation. LRRC8A plus LRRC8C/D/E, SLCO2A1, and TMEM206 were shown to be the core or pore-forming molecules of the volume-sensitive outwardly rectifying anion channel (VSOR) also called the volume-regulated anion channel (VRAC), the large-conductance maxi-anion channel (Maxi-Cl), and the acid-sensitive outwardly rectifying anion channel (ASOR) also called the proton-activated anion channel (PAC) in 2014, 2017, and 2019, respectively. More recently in 2020 and 2021, we have identified the S100A10-annexin A2 complex and TRPM7 as the regulatory proteins for Maxi-Cl and VSOR/VRAC, respectively. In this review article, we summarize their biophysical and structural properties as well as their physiological roles by comparing with each other on the basis of their molecular insights. We also point out unsolved important issues to be elucidated soon in the future.